Towards a new FRET system via combination of pyrene and perylene bisimide: synthesis, self-assembly and fluorescence behavior - Wang, Gang; Chang, Xingmao; Peng, Junxia; Liu, Kaiqiang; Zhao, Keru; Yu, Chunmeng; Fang, Yu (Physical chemistry chemical physics : PCCP, 2015)
A new fluorescent derivative of cholesterol, N,N'-(N-(2-(3β-cholest-5-en-3yl-formamido)ethyl) pyrene-1-sulfonamido)ethyl perylene-3,4:9,10-tetracarboxylic acid bisimide (CPPBI), was designed and synthesized. In the design, pyrene (Py) and perylene bisimide (PBI) were specially chosen as the energy donor and the acceptor, respectively. Fluorescence studies revealed that (1) CPPBI shows a strong tendency to form supra-molecular assemblies, (2) the assemblies possess a high efficiency of fluorescence resonance energy transfer (FRET) via intermolecular interactions, and (3) the profile and position of its fluorescence emission are highly dependent upon the nature of its medium, but the medium shows little effect on the efficiency of the energy transfer, suggesting that the chromophores including both Py and PBI units enjoy some rotational and/or translational mobility in the aggregated state of the compound. Temperature- and concentration-dependent (1)H NMR spectroscopy studies revealed that both hydrogen-bonding and π-π stacking play a great role in stabilizing the assemblies of the compound, and confirmed the existence of π-π stacking between the Py moieties and between the PBI residues of the compound, of which the donor and the acceptor may have arranged in an appropriate orientation and at a suitable distance which are the key factors to determine the FRET efficiency. Moreover, the CPPBI-based film possesses unusual photochemical stability, and its emission is sensitive to the presence of some organic vapors, in particular aniline.